2020
DOI: 10.26434/chemrxiv.12678860.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Kinetic Study of the Melanogenesis from Select Catecholamines in the Presence of L-Cysteine or Other Amino Acids

Abstract: <p>This report is a continuation of an earlier report on the effect of L-cysteine on the synthesis of melanin-like materials from catecholamines. We confirmed the pattern of results indicating that in the presence of L-cysteine the appearance of dark colors during the melanogenesis reactions is delayed, but that ultimately the presence of L-cysteine yields reaction mixtures with darker colors. The results of the current report indicate that the effect of L-cysteine is very reproducible in the cases of DO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 46 publications
2
8
0
Order By: Relevance
“…Overall, the current observations strengthen our hypothesis that MN materials are built from at least two types of substances: 1) a soluble, yellow-to-orange colored component, rich in unoxidized precursors and 2) an insoluble, dark component. In addition, our earlier experiments [2][3] and other reports 15, 19-20, 32, 40-42 indicate that the ratio of the various reaction products generated, and/or their physic-chemical properties, may depend on the reaction conditions applied.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Overall, the current observations strengthen our hypothesis that MN materials are built from at least two types of substances: 1) a soluble, yellow-to-orange colored component, rich in unoxidized precursors and 2) an insoluble, dark component. In addition, our earlier experiments [2][3] and other reports 15, 19-20, 32, 40-42 indicate that the ratio of the various reaction products generated, and/or their physic-chemical properties, may depend on the reaction conditions applied.…”
Section: Discussionmentioning
confidence: 55%
“…Building upon earlier observations and the hypotheses derived from them, we explored further the possibility that melanins (MNs), synthesized through air-oxidation in an alkaline environment, consist of at least two distinctly different types of materials. [1][2][3] We observed that from within the dark-brown to black material typically generated during the MN synthesis process, one can extract substances that possess a much lighter (orange to yellow) color. We have expanded these observations in part with the inclusion of catechol and pyrogallol as precursors for MN-like materials.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19] Our current report is a combination of results obtained from new experiments and through an evaluation of experimental data collected over the past three years; some of which have been detailed elsewhere. [20][21][22][23][24][25] In these previous reports we detailed and discussed observations that this current report expands on and integrates into one overarching theme about the balance between EuMN and PhMN:…”
Section: Introductionmentioning
confidence: 99%
“…22 2) The addition of other amino acids (AA) appeared to inhibit, but not delay, the formation of any colored material and to yield reaction mixtures with different UV-Vis absorbance profiles. 24 3) The post-synthesis precipitation of EuMN-like materials yielded supernatants that contained materials that in appearance and in other properties were PhMN-like; although no C was present during the synthesis of these materials. 23 4) Our previous observations prompted us to hypothesize that the synthesis of EuMN leads to a mixture of at least two different sets of materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation